Microstructure—Machinability correlation in heat treated AISI 1040 steel: Comparative analysis of tool life and surface roughness - Umanath R. Poojary; Ananda Hegde; Sriharsha Hegde; Rayappa Shrinivas Mahale (PLoS ONE, 2026)
This study presents an integrated investigation of the machinability of heat treated AISI 1040 steel under annealed, normalized, and oil quenched conditions. The effects of heat treatment parameters, namely austenitizing temperature and soaking time, together with machining parameters including cutting speed, feed rate, and depth of cut, were evaluated in terms of tool life and surface roughness. Experiments were designed using a Taguchi L27 orthogonal array, and the responses were analyzed through analysis of variance (ANOVA), regression modeling, and optimization techniques. The results showed that temperature, cutting speed, and feed rate significantly influenced tool life, whereas feed rate was the most dominant factor affecting surface roughness in all heat treatment conditions. Annealed AISI 1040 steel exhibited the highest tool life and the best overall machinability because of its relatively softer ferrite-pearlite microstructure, while oil quenched specimens showed the lowest tool life due to the formation of hard martensitic phases. Normalized specimens displayed intermediate behavior, indicating a balanced combination of strength and machinability. The developed regression models showed good predictive capability for both tool life and surface roughness within the investigated parameter range. SEM analysis further confirmed that the observed variations in machinability were closely associated with microstructural evolution caused by different heat treatment routes. The study provides useful guidance for selecting suitable heat treatment and machining parameters to improve productivity, tool performance, and surface quality during machining of AISI 1040 steel.